Droplets impact on sparse microgrooved non-wetting surfaces - Longfei Zhang; Jialong Wu; Yingfa Lu; Yingsong Yu (Scientific Reports)
Abstract Droplets impinging on sparse microgrooved polydimethylsiloxane (PDMS) surfaces with different solid fractions was experimentally investigated. First, wettability and stability of droplets on these surfaces was analyzed. The advancing and receding contact angles were found to have a large difference between in the longitudinal direction and in the transverse one, which could be attributed to the anisotropy of the micropatterned surfaces. The judgement of whether a droplet on a sparse microgrooved structure is collapsed or suspended is proposed, and it was found that the droplets were in the Cassie-Baxter wetting state when the actual contact line density is greater than the critical contact line density, while they were in the Wenzel wetting state otherwise. Second, for the case of droplets impacting on sparse microgrooved PDMS surfaces, it was found that droplets can bounce off the micro-patterned surface with a solid fraction of 0.158 when the impact velocity was in a certain range. The lower limit of impact velocity for bouncing droplets can be determined by balancing the kinetic energy of the droplets with the energy barrier due to contact angle hysteresis. The upper limit of impact velocity for bouncing droplets was predicted using a theoretical model taking into account the penetration of liquid into the cavities between microstripes.